2020
DOI: 10.1002/psp4.12486
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Simulation To Optimize Trial Design for Fludarabine Dosing Strategies in Allogeneic Hematopoietic Cell Transplantation

Abstract: Optimal fludarabine exposure has been associated with improved treatment outcome in allogeneic hematopoietic cell transplantation, suggesting potential benefit of individualized dosing. A randomized controlled trial (RCT) comparing alternative fludarabine dosing strategies to current practice may be warranted, but should be sufficiently powered for a relevant end point, while still feasible to enroll. To find the optimal design, we simulated RCTs comparing current practice (160 mg/m 2 ) to either covariate-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Recently, Punt et al developed an LC–MS/MS method for the simultaneous quantitation of busulfan, clofarabine, and fludarabine in plasma [ 28 ]. This method has been applied to study the population PKs of fludarabine and clofarabine [ 33 , 34 , 35 ]. The combination of busulfan and fludarabine, with or without clofarabine, is currently emerging as an HCT conditioning regimen [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Punt et al developed an LC–MS/MS method for the simultaneous quantitation of busulfan, clofarabine, and fludarabine in plasma [ 28 ]. This method has been applied to study the population PKs of fludarabine and clofarabine [ 33 , 34 , 35 ]. The combination of busulfan and fludarabine, with or without clofarabine, is currently emerging as an HCT conditioning regimen [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…with respect to enrolment numbers (e.g. phase I studies) (9)(10)(11)32). Dickinson et al demonstrated the utility of virtual pharmacogenetic trials using the example of warfarin and CYP2C9 polymorphisms, though without power analyses (33).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the latter non-model-based approaches conventionally only consider one single time point of the concentration-or effect-time profile (8). The utility of clinical trial simulations and model-based data analysis methods to inform the design of clinical studies has been demonstrated across various therapeutic fields (9)(10)(11). In pharmacogenomics, pharmacometric models have foremost been used to enhance the understanding of the impact of genetic variants on drug exposure and various outcomes rather than for clinical trial design.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in clofarabine clearance relating to renal function is a gradual process and even an eGFR below 120 mL/min/1.73 m 2 is associated with a decrease in clofarabine clearance and concomitant higher exposures, 4 which makes a dose algorithm, taking renal function into account, more suitable to decide which dose should be administered. This approach has been described previously for other drugs, for example carboplatin and fludarabine 25–27 . Such a dosing algorithm for clofarabine was derived from this PK model (Equation 5); however, a target AUC is needed to calculate the conventional clofarabine dose.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been described previously for other drugs, for example carboplatin and fludarabine. 25 , 26 , 27 Such a dosing algorithm for clofarabine was derived from this PK model (Equation 5 ); however, a target AUC is needed to calculate the conventional clofarabine dose. A target AUC for clofarabine during conditioning prior to HCT has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%